Therapeutic anti-inflammatory immune potentials of some seaweeds extracts on chemically induced liver injury in mice - Eman Bases; Mostafa M. El-Sheekh; Shimaa M. El Shafay; Rania El-shenody; Mohamed Nassef (Scientific Reports)
Abstract Carbon tetrachloride (CCl4) is a well-known hepatotoxin. This work aimed to assess the therapeutic anti-inflammatory immune potentials of the seaweeds Padina pavonia and Jania rubens extracts on carbon tetrachloride (CCL4)-caused liver damage in mice. Our experimentation included two testing regimens: pre-treatment and post-treatment of P. pavonia and J. rubens extracts in CCL4/mice. Pre-treatment and post-treatment of P. pavonia and J. rubens extracts in CCL4/mice increased WBCs count and lymphocytes relative numbers and reduced the neutrophils and monocytes relative numbers. Pre-treatment and post-treatment of CCL4/mice with P. pavonia and J. rubens extracts significantly reduced the release amounts of pro-inflammatory cytokines TNF-α and IL-6 and significantly inhibited the increased CRP level. Furthermore, pre-treatment and post-treatment of CCL4/mice with P. pavonia and J. rubens extracts recovered the activities of GSH, and significantly decreased MDA level. CCL4/mice pre-treated and post-treated with P. pavonia and J. rubens extracts decreased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels. Pre- and post-treatment of CCL4/mice with the P. pavonia and J. rubens extracts ameliorated the liver damages caused by CCl4 and significantly inhibited the necrotic area, indicating hepatic cell death and decreased periportal hepatic degeneration, fibrosis, and inflammation.